2006
DOI: 10.1128/aem.72.1.167-177.2006
|View full text |Cite
|
Sign up to set email alerts
|

Deoxysugar Transfer during Chromomycin A 3 Biosynthesis in Streptomyces griseus subsp. griseus : New Derivatives with Antitumor Activity

Abstract: Chromomycin A 3 (Fig. 1A) is an antitumor drug produced by Streptomyces griseus and other streptomycete species. It belongs to the class of antitumor compounds of the aureolic acid family (22), which inhibit growth and multiplication of several tumor cell lines. The antitumor properties are ascribed to their inhibitory effects on replication and transcription processes during macromolecular biosynthesis by interacting, in the presence of Mg 2ϩ , with GC-rich nucleotide sequences located in the minor groove of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
1
38
0
1
Order By: Relevance
“…The structure of 11 matches earlier discussions that concluded that CmmGIV, the glycosyltransferase responsible for the transfers of both sugars A and E, actually transfers 4-ketosugars, which are reduced after the attachment, presumably by CmmTIII (10). Thus, compound 11 might indeed be an (instable) intermediate of the chromomycin A 3 biosynthetic pathway.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The structure of 11 matches earlier discussions that concluded that CmmGIV, the glycosyltransferase responsible for the transfers of both sugars A and E, actually transfers 4-ketosugars, which are reduced after the attachment, presumably by CmmTIII (10). Thus, compound 11 might indeed be an (instable) intermediate of the chromomycin A 3 biosynthetic pathway.…”
Section: Resultssupporting
confidence: 81%
“…The isolation of compounds from inactivation of CmmA and CmmMIII yielded chromomycin A 3 derivatives with missing acetyl and methyl decorations, and the di-deacetyl-chromomycin A 3 appears to be a substrate for the out-transporters CmrAB (26). On the other hand, mutants in which glycosyltransfer steps affecting sugar units B alone or both A and B, respectively, were inactivated and yielded still tricyclic tetrasaccharidal and tetracyclic trisaccharidal prechromomycins with already O -acetylated sugar moieties A and/or E (10). While these contradictive results could be explained by substrate flexibility of the sugar decorating enzymes, a potential substrate flexibility of key oxygenase CmmOIV is an alternative.…”
mentioning
confidence: 99%
“…In the past decades, a number of aureolic acid analogs were obtained from genetically engineered mutant producers showing distinct structural changes. [5][6][7][8] This has yielded in some information on the structure-activity relationship of this type of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was identified that premithramycin B was transformed into an aureolic acid structure by oxygenase MtmOIV through fourth ring Baeyer-Villiger oxidative cleavage [26] . The enzyme homologue to cyclase MtmOIV was also identified in the biosynthetic gene cluster of chromomycin A 3 [2] derived from prechromomycin B, which is a tetracylic intermediate [27] .…”
Section: Resultsmentioning
confidence: 99%